2020
DOI: 10.1007/s10648-020-09571-9
|View full text |Cite
|
Sign up to set email alerts
|

Generative Learning: Which Strategies for What Age?

Abstract: Generative learning strategies are intended to improve students’ learning by prompting them to actively make sense of the material to be learned. But are they effective for all students? This review provides an overview of six popular generative learning strategies: concept mapping, explaining, predicting, questioning, testing, and drawing. Its main purpose is to review for what ages the effectiveness of these strategies has been demonstrated and whether there are indications of age-related differences in thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 102 publications
(129 reference statements)
3
37
0
1
Order By: Relevance
“…The null findings regarding students' comprehension might be attributed to low levels of prior knowledge. Little prior knowledge limits students in learning new contents adequately [30,84]. However, prior research revealed that generative learning activities, such as explaining, are in particular beneficial for low prior knowledge students [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The null findings regarding students' comprehension might be attributed to low levels of prior knowledge. Little prior knowledge limits students in learning new contents adequately [30,84]. However, prior research revealed that generative learning activities, such as explaining, are in particular beneficial for low prior knowledge students [9].…”
Section: Discussionmentioning
confidence: 99%
“…Then, they need to connect the new contents with their already existing knowledge to integrate them into their long-term memory [27,29,30]. Through this connection, students are able to provide explanations that include further details and information that go beyond the giving materials, which results in new knowledge and meaningful learning [27][28][29][30][31][32][33][34]. This process additionally triggers students to monitor whether they understood all relevant contents correctly or whether they need to restudy specific information.…”
Section: Learning By Explaining To Fictitious Peersmentioning
confidence: 99%
“…From a psychological perspective, we are talking about the effects of (a) agency beliefs, (b) prior-knowledge activation, (c) cognitive capacities for sense making, and (d) metacognitive capacities for self-reflection. As briefly summarized in the next section, all of these psychological constructs have been intensively researched, and their developmental trajectory is well known (for a more detailed account, see Brod, 2020). This summary provides the basis for the quintessence of this commentary, which is that knowledge of developmental trajectories and the effects they have on learning can guide our understanding of how to make active-learning practices work in K–12 education and beyond.…”
mentioning
confidence: 99%
“…In line with the generative learning theory, the process of explaining as a generative act may elicit cognitive (e.g., mental effort) and metacognitive (e.g., monitoring) processes, which should contribute to students' comprehension: First, and in line with Mayer's SOI model [28], when explaining students need to select the most relevant information if the provided materials and to organize the information in a coherent way. Then, they need to connect the new contents with their already existing knowledge to integrate them into their long-term memory [27,29,30]. Through this connection, students are able to provide explanations that include further details and information that go beyond the giving materials, which results in new knowledge and meaningful learning [27][28][29][30][31][32][33][34].…”
Section: Learning By Explaining To Fictitious Peersmentioning
confidence: 99%
“…Additionally, results indicated a higher correlation between prior knowledge and students' learning outcome, suggesting that the provided learning material was too difficult, which may explain the null findings. Seemingly, students have problems in applying this learning strategy successfully when the learning material is overly difficult [30], which highlights the need for additional support during learning, such as pre-trainings or prompts [39,43,95].…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%